COMPUTATIONAL FLUID DYNAMIC (CFD) SIMULATION ON REDESIGN BAFFLES OF YOGYAKARTA INTERNATIONAL AIRPORT TRAIN FUEL TANK - Putri Novia; Bi Asngali; Agus Susanto; Riant Adzandy; Hedi Purnomo (Media Mesin: Majalah Teknik Mesin, 2023)
The tank is one of the most important components in the train which serves as a place to store train fuel. However, so far the tank has been a component that has gone unnoticed, even though there is a very important issue to consider, namely how the fluid moves in the tank due to the movement of the train while moving. The free movement of the liquid fluid in a tank is called sloshing. Sloshing in the tank can be reduced by adding anti-sloshing in the tank called component baffles. So it is necessary to simulate the sloshing due to the movement of the train by taking into account the value of the vehicle subsystem of the train and the variation of the baffles design used. There are several models of fuel tank baffles used in this study, namely fuel tanks without baffles; longitudinal baffles (2) lateral baffles (1) - existing baffles; longitudinal baffles (3) lateral baffles (3) with circular perforations; and horizontal (2) lateral (1) baffles with circular perforations. This study aims to provide a baffles design configuration that can optimally reduce the sloshing that occurs. So in this study, a simulation of the fuel tank with variations in the baffles was carried out by applying the Computational Fluid Dynamic (CFD) method. From the simulation results, it is concluded that the configuration of longitudinal baffles (3) lateral baffles (3) has the best performance with an effectiveness of 34.33% in reducing sloshing.